Plyometric Upper Limb Training for Over-the-Shoulder Shot in Softball (Impetus, 2021)
In conventional training for this sport, physical preparation has a great emphasis on the development of maximum strength, leaving aside other methods of strength development that may be more beneficial due to the different muscular components involved and the motor richness that generate, as is the case of the development of strength, there was inter and intra muscular or explosive coordination, which widely uses the Arctic component and which are also more consistent with the actions of the game